1980
DOI: 10.1159/000123098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substance P on Anterior Pituitary Secretion in the Female Rhesus Monkey

Abstract: The effects of substance P on anterior pituitary secretion were studied in 3 female rhesus monkeys. In nine experiments, 100 μg substance P was injected intraventricularly, and the results were compared to those obtained following intraventricular injection of the control vehicle. In 7 out of 9 experiments, substance P induced a significant increase in prolactin secretion within 5 min. Peak levels at 10 min were approximately 15-20 times those of the baseline control. Substance P also induced a slight but sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Other investigators (23) reported increased in vitro release of somatostatin from hypothalamic fragments incubated in the presence of SP, which supports the concept that the central inhibitory effect of SP on GH may be mediated by somatostatin. On the other hand, Takahara et al (24) found that intraventricularly injected SP itself had no effect on serum GH, but it inhibited the y-aminobutyric acid-induced increases in serum GH. In the rhesus monkey, SP was also reported to induce a significant decrease in GH secretion (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators (23) reported increased in vitro release of somatostatin from hypothalamic fragments incubated in the presence of SP, which supports the concept that the central inhibitory effect of SP on GH may be mediated by somatostatin. On the other hand, Takahara et al (24) found that intraventricularly injected SP itself had no effect on serum GH, but it inhibited the y-aminobutyric acid-induced increases in serum GH. In the rhesus monkey, SP was also reported to induce a significant decrease in GH secretion (24).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Takahara et al (24) found that intraventricularly injected SP itself had no effect on serum GH, but it inhibited the y-aminobutyric acid-induced increases in serum GH. In the rhesus monkey, SP was also reported to induce a significant decrease in GH secretion (24).…”
Section: Discussionmentioning
confidence: 99%
“…From several reports, SP has been shown to stimulate the release of PRL from anterior pituitary cells in vivo as well as in vitro (Eckstein et al, 1980;Chihara et al, 1978;Vijayan and McCann, 1978;Kat0 et al, 1976). The presence of [ lZ5I]-BH-SP binding sites on PRGcontaining cells provides evidence that SP exerts its prolactinreleasing action directly on mammotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo as well as in vitro, SP has been shown to stimulate the release of prolactin (PRL) from anterior pituitary cells (Eckstein et al, 1980;Chihara et al, 1978;Vijayan and McCann, 1978;Kat0 et al, 1976). In addition to its action on lactotrophs, SP is likely to influence gonadouophs.…”
Section: Introductionmentioning
confidence: 99%
“…Substance P injected into the lateral ventricle of female Rhesus monkey increased prolactin and decreased growth hormone concentrations in serum (15), while in the rat these effects were variable, perhaps depending on the concentration employed (16)(17)(18)(19)(20). The effect on LH is controversial and depends on the species studied, the route of administration and sex-steroid hormonal status (16)(17)(18)21).…”
Section: Introductionmentioning
confidence: 99%